Identificação de mutações no gene codificador da proteína spike do SARS-CoV-2 no Estado do Espírito Santo - Paula, Isabelle Barroso de (2022)
SARS-CoV-2 is a coronavirus that has a surface glycoprotein (S) that plays an essential role in binding through the formation of trimers with the S protein and Angiotensin Converting Enzyme 2 (ACE2) amino acids present in the cell. host. S glycoprotein is crucial for determining host tropism, through ACE2, and transmission capacity, mediating receptor binding (ACE2) and cell membrane fusion. Certain comorbidities are associated with a strong expression of the ACE2 receptor and greater release of proprotein convertase that increases viral entry into host cells, therefore, it is necessary to investigate the mutations and the infection status of patients with COVID-19 in the state. of the Holy Spirit. The analysis of samples collected from patients, from June 2020 to May 2021, in the State of Espírito Santo revealed the existence of 269 mutations in the Spike protein. The most frequent mutations were N501Y, E484K, K417N and D427N, respectively in 20.44%, 34.57%, 20.07% and 1.49%. Among the mutations detected, 5 belong to the variants of concern Alpha (B.1.1.7), Beta (B.1.135) and Gamma (P.1). Comparison of mutations with clinical pathological data was performed by Fisher's Exact Test, for comparison of two independent samples. When evaluating the symptoms and comorbidities, we did not observe any significance regarding the severity of the symptoms and the presence of comorbidity among the patients. We conclude that the virus has a high mutational capacity and that the mutations detected in Espírito Santo do not differ from the rest of the world.